2022
DOI: 10.2147/cia.s351226
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Validation of a Nomogram to Predict Hospital-Acquired Infection in Elderly Patients After Cardiac Surgery

Abstract: Background: Hospital-acquired infection (HAI) after cardiac surgery is a common clinical concern associated with adverse prognosis and mortality. The objective of this study is to determine the prevalence of HAI and its associated risk factors in elderly patients following cardiac surgery and to build a nomogram as a predictive model. Methods: We developed and internally validated a predictive model from a retrospective cohort of 6405 patients aged ≥70 years, who were admitted to our hospital and underwent car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…A previous study has shown the duration of mechanical ventilation is related to an incremented risk of infection, even moderately prolonged ventilation (24 h versus 48 h). Consistent with the finding of this study, other studies also demonstrated a strong correlation between the duration of mechanical ventilation and the risk of infection (Ailawadi et al, 2017; Atladottir et al, 2021; Gao et al, 2022; Hassoun‐Kheir et al, 2020). The data from the above studies suggest that clinical staff should comprehensively evaluate the patient's physical condition and shorten the duration of mechanical ventilation as much as possible.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A previous study has shown the duration of mechanical ventilation is related to an incremented risk of infection, even moderately prolonged ventilation (24 h versus 48 h). Consistent with the finding of this study, other studies also demonstrated a strong correlation between the duration of mechanical ventilation and the risk of infection (Ailawadi et al, 2017; Atladottir et al, 2021; Gao et al, 2022; Hassoun‐Kheir et al, 2020). The data from the above studies suggest that clinical staff should comprehensively evaluate the patient's physical condition and shorten the duration of mechanical ventilation as much as possible.…”
Section: Discussionsupporting
confidence: 90%
“…Patients who have undergone cardiac surgery, including valve replacement, are prone to postoperative complications, and NIs are one of the more common ones (Gelijns et al, 2014). Poor physical condition and invasive procedures, including prolonged mechanical ventilation and cardiopulmonary bypass, are possible reasons for VHD patients' susceptibility to developing NIs (de la Varga‐Martínez et al, 2021; Gao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al . established a nomogram for predicting infections acquired in a hospital among elderly patients after cardiac surgery to achieve better preoperative management 14 . Another study by Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…13 Gao et al established a nomogram for predicting infections acquired in a hospital among elderly patients after cardiac surgery to achieve better preoperative management. 14 Another study by Liu et al found that a nomogram to predict anastomotic leakage among elderly patients with rectal cancer had satisfactory accuracy and may benefit clinical decision making. 15 Yet, to the best of our knowledge, there are currently no such valuable tools available for predicting postoperative complications among elderly patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in East African countries, where surveillance capacity is minimal, reducing the impact of infections remains an unsolved challenge. Moreover, despite a wide range of risk factors contributing to the occurrence of infections in critically ill patients that have been described in developed countries [ 2 , 3 , 4 , 5 ], to the best of our knowledge, little information is available on this topic in cardiac surgery ICUs in low-income settings.…”
Section: Introductionmentioning
confidence: 99%